Impact of building morphology and outdoor environment on light and thermal environment in campus buildings in cold region during winter. (15th October 2021) - Wang, Shibo; Chen, Bin; Suo, Jian; Zhao, Joe R.
Abstract: Light and thermal environments are important factors in designing campus buildings. The existing research on human-centered indoor environment needs is insufficient. Hence, it is difficult to comprehensively evaluate the indoor light and thermal environmental quality. Therefore, we proposed "time satisfaction rate of the comprehensive light and thermal environment requirements (TSR)" and "spatial satisfaction rate of the comprehensive light and thermal environment requirements (SSR), " evaluation indicators that comprehensively accounted for visual, photobiological, and thermal comfort requirements. The study was conducted in the winter on campus buildings located in a cold region with central heating. We analyzed the effects of building morphology, orientation, and outdoor environment on the light and thermal environment in classrooms and offices using field-measured data. The light environment was regulated according to occupants' individual demands during our research. The results showed that the TSRs of east-facing and west-facing offices were 67% and 33% lower than the TSRs of the south-facing office and 33% and 33% lower than the TSRs of the north-facing office on clear and overcast days, respectively. Moreover, the SSR of north-facing classrooms was 16.5% and 8.3% higher than that of the south-facing classrooms on clear and overcast days, respectively. Measures to prevent the glare from east-facing and west-facing facades of the building bulge reduced the illuminance and CS by 10%. Our research provides reference and basis for improving the design of light and thermal environments to fulfill occupants' needs in a comprehensive and human-centered method. Highlights: The evaluation indicators based on human-centered TSR and SSR are proposed. The demand-oriented environment control mode of campus buildings is described. The impact of morphology and orientation on light-thermal needs are analyzed.